Factors Affecting Operation Duration in Posterior Spinal Fusion (PSF) Using Dual Attending Surgeon Strategy Among Lenke 1 and 2 Adolescent Idiopathic Scoliosis (AIS) Patients. Issue 1 (February 2022) - Chung, Weng Hong; Mihara, Yuki; Chiu, Chee Kidd; Hasan, Mohd Shahnaz; Chan, Chris Yin Wei; Kwan, Mun Keong
Abstract : Study Design: This was a retrospective study. Summary of Background Data: Prolonged operation duration in adolescent idiopathic scoliosis (AIS) surgery was associated with increased perioperative complications. However, the factors affecting operation duration in AIS surgery were unknown. Objective: The aim of the study was to investigate the factors affecting operation duration in posterior spinal fusion (PSF) surgery using a dual attending surgeon strategy among Lenke 1 and 2 AIS patients. Methods: In all, 260 AIS patients with Lenke 1 and 2 curves who underwent PSF were retrospectively reviewed. Preoperative and intraoperative factors affecting operation duration such as age, sex, height, weight, body mass index, Risser grade, Lenke subtypes, number of fusion level, number of screws, screw density, wound length, upper and lowest instrumented vertebrae level, preoperative Cobb angle, and flexibility of the major curve were assessed using univariate and multivariate linear regression analyses. Independent factors were determined when P -value <0.05. Results: The mean operation duration was 122.2±28.6 minutes. Significant independent factors affecting operation duration in PSF among Lenke 1 and 2 AIS patients were Lenke 2 subtypes (β=8.86, P =0.008), number of screws (β=7.01, P <0.001), wound length (β=1.14, P =0.009), and flexibility of the major curve (β=−0.25, P =0.005). The overall model fit was R 2 =0.525. Operation duration can be predicted using the formula: (8.86×Lenke subtypes)+(7.01×number of screws)+(1.14×wound length)−(0.25×flexibility)−0.54, where Lenke 2=1 and Lenke 1=0. Conclusion: The factors affecting operation duration in PSF among Lenke 1 and 2 AIS patients were Lenke 2 curves, number of screws, wound length, and curve flexibility. The knowledge of these factors enables the spinal deformity surgeons to plan and estimate the operation duration before AIS surgery.